Preparation method and application of CuBi2O4 film electrode
Cu2O film electrodes were prepared by electrodeposition and converted into CuBi2O4 film electrodes, which solved the problems of large interface resistance and low charge carrier mobility of existing photoelectrode materials, and achieved efficient photocatalytic decomposition of water and hydrogen production. The process was simple ,Environmental friendly.
Patent Information
- Application Number
- CN202411575851.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
The existing metal oxide semiconductor photoelectrodes have poor photoelectric conversion efficiency due to their large interface resistance, low charge carrier mobility and unstable reaction kinetics, which limits their application in PEC water decomposition.
Cu2O film electrodes were prepared by electrodeposition method and converted into CuBi2O4 film electrodes through lifting impregnation and annealing reactions. The surface state was optimized using high crystallinity covalent organic frame (COFs) materials and K ions to reduce the interface resistance.
The prepared CuBi2O4 thin film electrode has high crystallinity, controllable morphology, and significantly improved the photocatalytic hydrogen production rate, reaching 4 times the activity of synthesis of isoform materials in traditional methods. It has simple process, easy parameters to control, and is green and environmentally friendly.
Smart Images

Figure CN119433580A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a CuBi2O4 thin film electrode and application thereof, belonging to the field of thin film materials. Background Art
[0002] In today's society, the increasingly serious energy crisis and environmental problems force people to explore clean and renewable energy to replace traditional fossil energy. Hydrogen has a high energy density and its combustion product is water, which is almost zero emission. Therefore, hydrogen energy is a new type of clean and renewable energy with great potential. Photoelectrochemical water splitting cells can convert the world's largest amount of renewable solar energy into storable hydrogen energy. The development of high-performance semiconductor photoelectrode materials is the only way to achieve photoelectrochemical water splitting cells with high energy conversion efficiency.
[0003] An ideal photoelectrode requires not only a suitable band gap, but also good resistance to light and electrical corrosion. However, most metal oxide semiconductor photoelectrodes reported so far have relatively poor photoelectric conversion efficiencies due to large contact resistance, low charge carrier mobility, reaction kinetics, and instability caused by self-photoelectric corrosion when in contact with electrolyte solutions, which limits their application and competitiveness in PEC water splitting.
[0004] Therefore, it is necessary to explore new methods to prepare CuBi2O4 thin film electrodes to reduce the interface resistance caused by lattice mismatch between substrate and CuBi2O4, so as to prepare thin film electrodes with better quality. Summary of the invention
[0005] In order to solve the problems existing in the prior art, one of the purposes of the present invention is to provide a method for preparing a CuBi2O4 thin film electrode, and the specific steps are as follows:
[0006] (1) Add copper acetate and sodium acetate to deionized water and mix well to obtain electrolyte I, put FTO into electrolyte I, and obtain a Cu2O thin film electrode by electrodeposition.
[0007] (2) Add a complexing agent to the bismuth nitrate solution to obtain emulsion II.
[0008] (3) Add KOH to the emulsion II in step (2) to obtain a clear solution III.
[0009] (4) adjusting the molar concentration of potassium nitrate to 0.25-1 mol / L on the basis of the clarified solution III to obtain solution IV; adding potassium nitrate when the molar concentration of potassium nitrate in step (3) is less than the required concentration; and diluting with water when the molar concentration of potassium nitrate in step (3) is greater than the required concentration.
[0010] (5) The Cu2O thin film electrode obtained in step (1) is pulled and immersed in solution IV obtained in step (4), and then annealed. The annealed electrode is washed with deionized water and dried to obtain a CuBi2O4 thin film electrode.
[0011] Preferably, the molar concentration of copper acetate in the electrolyte I in step (1) is 0.05 mol / L to 0.2 mol / L, the molar concentration of sodium acetate is 0.05 mol / L to 0.2 mol / L, and the molar ratio of copper acetate to sodium acetate is 1:1.
[0012] Preferably, the conditions of the electrodeposition method in step (1) are: applying a bias voltage of -0.2 V to the FTO substrate and the electrodeposition time is 120 s.
[0013] Preferably, in step (2), the volume ratio of the bismuth nitrate solution to the complexing agent is 95:5 to 99:1, the molar concentration of the bismuth nitrate solution is 0.05 mol / L to 0.2 mol / L; and the complexing agent is triethanolamine.
[0014] Preferably, the amount of KOH added to the emulsion II in step (3) is 0.001-2 mol / L.
[0015] Preferably, the pulling and dipping speed in step (5) is 0.05 to 0.5 cm / s.
[0016] Preferably, in step (5), the annealing process temperature is 450° C., and the reaction time is 2 h; the drying temperature is 50-80° C., and the drying time is 3 h.
[0017] Another object of the present invention is to provide an application of the prepared CuBi2O4 thin film electrode in photoelectrocatalytic water decomposition to produce hydrogen.
[0018] Beneficial effects of the present invention
[0019] (1) The present invention first prepares a uniform and dense Cu2O thin film electrode by electrodeposition, and then converts it into a CuBi2O4 thin film electrode. The prepared CuBi2O4 thin film electrode has controllable morphology and high crystallinity. The highly crystalline covalent organic framework (COFs) material performs well in photocatalytic hydrogen production rate, which is 4 times more active than the isomorphic material synthesized by traditional methods.
[0020] (2) Bismuth hydroxide will react with KOH to form a complex, and the solution will become clear. The particle size of the generated bismuth hydroxide will grow from the nanometer scale to ensure uniform coverage on the surface of the Cu2O film to promote the reaction. However, the particle size of the purchased finished bismuth hydroxide is too large, and there is too little contact between bismuth hydroxide and the Cu2O film. Even if there is molten salt to promote the reaction, it is difficult to generate CuBi2O4.
[0021] (3) The thin film electrodes prepared by traditional methods such as drop coating, spin coating, and screen printing will increase the interface resistance of the electrode, which affects the photoelectrocatalytic performance of the thin film photoelectrode because the interface between the absorption layer material and the substrate material such as FTO is not fully compatible. The Cu2O template introduced by electrodeposition first, Cu2O is grown on FTO, which will greatly reduce its lattice mismatch problem and optimize the interface resistance between FTO and the photocatalytic material.
[0022] (4) By controlling Bi 3+ and Cu2O to synthesize CuBi2O4 films with the optimal ratio, and characterize the optical, electrical and photoelectrochemical properties of the final CuBi2O4 films to establish the relationship between film composition, structure and performance.
[0023] (5) The present invention introduces a molten salt reaction when making a thin film electrode to promote the reaction and improve its crystallinity to optimize its photoelectrocatalytic performance. Secondly, the K ions contained in the molten salt selected by the present invention can also optimize its surface state.
[0024] (6) The preparation process provided by the present invention has the advantages of simple method, easy control of parameters, green and environmental protection, high yield, rapidity and low cost. It can be widely used in copper-based oxide thin film electrodes, which is conducive to the development of new photoelectrodes and their application and industrial development in photoelectrocatalytic water decomposition to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the X-ray crystal diffraction pattern of the Cu2O thin film electrode prepared in Example 1.
[0026] Figure 2 This is a scanning electron microscope image of the Cu2O thin film electrode prepared in Example 1.
[0027] Figure 3 The X-ray crystal diffraction pattern of the CuBi2O4 thin film electrode prepared in Example 1.
[0028] Figure 4 Scanning electron microscope image of the CuBi2O4 thin film electrode prepared in Example 1.
[0029] Figure 5 The X-ray crystal diffraction pattern of the CuBi2O4 thin film electrode prepared in Example 2.
[0030] Figure 6 Scanning electron microscope image of the CuBi2O4 thin film electrode prepared in Example 2.
[0031] Figure 7The X-ray crystal diffraction pattern of the CuBi2O4 thin film electrode prepared for Comparative Example 1.
[0032] Figure 8 Scanning electron microscope image of the CuBi2O4 thin film electrode prepared in Comparative Example 1.
[0033] Fig. 9 Photocurrent density diagrams of CuBi2O4 thin film electrodes prepared for Example 1, Example 2 and Comparative Example 3.
[0034] Fig.10 Scanning electron microscope image of the CuBi2O4 thin film electrode prepared in Comparative Example 3. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0036] Example 1
[0037] This embodiment provides a method for preparing a CuBi2O4 thin film electrode, and the specific steps are as follows:
[0038] (1) 10 mmol of copper acetate and 10 mmol of sodium acetate were dissolved in 100 ml of deionized water to obtain electrolyte I. FTO was immersed in electrolyte I and a bias voltage of -0.2 V was applied to FTO. The electrodeposition time was 120 s to obtain a Cu2O thin film electrode.
[0039] (2) To 95 ml of 0.1 mol / L bismuth nitrate solution, add 5 ml of triethanolamine, a complexing agent, to obtain emulsion II.
[0040] (3) Add 0.05 mol KOH to the emulsion II in step (2) to obtain a clear solution III.
[0041] (4) The molar concentration of KNO3 in the clear solution III is controlled to be 1 mol / L. The molar concentration of KNO3 in the clear solution III is calculated to be 0.5 mol / L, which is less than 1 mol / L. Therefore, molten salt KNO3 is added to the clear solution III under strong stirring to obtain solution IV.
[0042] (5) The Cu2O thin film electrode obtained in step (1) is pulled and immersed in the solution IV obtained in step (4) at a speed of 0.2 cm / s, and then annealed at a temperature of 450°C for a reaction time of 2 h; the electrode is rinsed with deionized water and dried at 50°C for 3 h to obtain a CuBi2O4 thin film electrode.
[0043] The X-ray crystal diffraction pattern of Cu2O prepared in Example 1 is as follows Figure 1 As shown in FIG. 1 , the characteristic diffraction peaks of the PDF standard card JCPDS 78-0276 completely correspond to each other, indicating that the sample is a Cu2O thin film. The scanning electron microscope image of the Cu2O thin film electrode prepared in this specific embodiment is shown in FIG. Figure 2 shown.
[0044] The X-ray crystal diffraction pattern of the CuBi2O4 thin film electrode prepared in Example 1 is as follows: Figure 3 As shown, it completely corresponds to the characteristic diffraction peaks of PDF standard card JCPDS 71-1774, indicating that the sample is a CuBi2O4 thin film electrode.
[0045] The scanning electron microscope image of the CuBi2O4 thin film electrode prepared in Example 1 is as follows: Figure 4 shown.
[0046] The photoelectrocatalytic performance of the CuBi2O4 thin film electrode prepared in Example 1 is as follows: Fig. 9 As shown in the figure, the CuBi2O4 thin film electrode prepared with a concentration of 1 mol / L (1M) KNO3 has a conductivity of 39 mW / cm 2 , under 455nm monochromatic light, the test was carried out in an electrolyte of 0.5mol / LHBO3 (pH=9) containing H2O2, and the potential was 2.45mA / cm at 0.6V. 2 The photocurrent density.
[0047] Example 2
[0048] This embodiment provides a method for preparing a CuBi2O4 thin film electrode, and the specific steps are as follows:
[0049] (1) 5 mmol of copper acetate and 5 mmol of sodium acetate were dissolved in 100 ml of deionized water to obtain electrolyte I. FTO was immersed in electrolyte I and a bias voltage of -0.2 V was applied to FTO. The electrodeposition time was 120 s to obtain a Cu2O thin film electrode.
[0050] (2) To 95 ml of 0.1 mol / L bismuth nitrate solution, add 5 ml of triethanolamine, a complexing agent, to obtain emulsion II.
[0051] (3) Add 0.05 mol KOH to the emulsion II in step (2) to obtain a clear solution III.
[0052] (4) The molar concentration of KNO3 in the clarified solution III was calculated to be 0.5 mol / L, which was greater than 0.25 mol / L. 100 ml of deionized water was added to the clarified solution III obtained in step (3) to obtain solution IV.
[0053] (5) The Cu2O thin film electrode obtained in step (1) is pulled and immersed in the solution IV obtained in step (5) at a speed of 0.2 cm / s, and then annealed at a temperature of 450°C for a reaction time of 2 h. The obtained electrode is rinsed with deionized water and dried at 70°C for 3 h to obtain a CuBi2O4 thin film electrode.
[0054] The X-ray crystal diffraction pattern of the Cu2O prepared in this embodiment and the scanning electron microscope image of the Cu2O thin film electrode prepared are similar to those in Example 1.
[0055] The X-ray crystal diffraction pattern of the CuBi2O4 thin film electrode prepared in this embodiment is as follows: Figure 5 As shown, it partially corresponds to the characteristic diffraction peaks of PDF standard card JCPDS 71-1774, indicating that the sample is a mixed phase of CuBi2O4 and Bi2O3.
[0056] The scanning electron microscope image of the CuBi2O4 thin film electrode prepared in this example is as follows: Figure 6 As shown in the figure, the surface of the CuBi2O4 thin film electrode contains Bi2O3 particles. This is because the solution environment has changed after the addition of water, resulting in the OH in the solution. - The concentration of Bi is less than that of Example 1. 3+ It may exist in the form of precipitates, which cannot fully contact the Cu2O template during the reaction and can only accumulate on the electrode surface. In addition, the addition of water dilutes solution III, which reduces the concentration of KNO3 and affects the subsequent solid phase reaction.
[0057] The photoelectrocatalytic performance of the CuBi2O4 thin film electrode prepared in this example is as follows Fig. 9 As shown in Figure 2, when the concentration of KON is 0.25 mol / L (0.25 M), the 2 , under 455nm monochromatic light, in the electrolyte environment of 0.5mol / LHBO3 (pH=9) containing H2O2, the current is 1.75mA / cm at a potential of 0.6V 2 The photocurrent density of CuBi2O4 thin film electrode was significantly decreased, indicating that the impure Bi2O3 particles would inhibit the photoelectrocatalytic performance of CuBi2O4 thin film electrode.
[0058] Example 3
[0059] This embodiment provides a method for preparing a CuBi2O4 thin film electrode, and the specific steps are as follows:
[0060] (1) 20 mmol of copper acetate and 20 mmol of sodium acetate were dissolved in 100 ml of deionized water to obtain electrolyte I. FTO was immersed in electrolyte I and a bias voltage of -0.2 V was applied to FTO. The electrodeposition time was 120 s to obtain a Cu2O thin film electrode.
[0061] (2) To 95 ml of 0.05 mol / L bismuth nitrate solution, add 5 ml of triethanolamine, a complexing agent, to obtain emulsion II.
[0062] (3) Add 0.05 mol KOH to the emulsion II in step (2) to obtain a clear solution III.
[0063] (4) The molar concentration of KNO3 in the clear solution III is controlled to be 1 mol / L. The molar concentration of KNO3 in the clear solution III is calculated to be 0.5 mol / L, which is less than 1 mol / L. Therefore, molten salt KNO3 is added to the clear solution III under strong stirring to obtain solution IV.
[0064] (5) The Cu2O thin film electrode obtained in step (1) is pulled and immersed in the solution IV obtained in step (4) at a speed of 0.2 cm / s, and then annealed at a temperature of 450°C for a reaction time of 2 h; the electrode is rinsed with deionized water and dried at 50°C for 3 h to obtain a CuBi2O4 thin film electrode.
[0065] The X-ray crystal diffraction pattern of the Cu2O prepared in Example 3 and the scanning electron microscope image of the Cu2O thin film electrode prepared are similar to those in Example 1.
[0066] The photoelectrocatalytic performance of the CuBi2O4 thin film electrode prepared in Example 3 is weaker than that in Example 1, indicating that reducing Bi 3+ concentration, the performance of the prepared Cu-rich sample is slightly inferior to that of pure CuBi2O4.
[0067] Example 4
[0068] This embodiment provides a method for preparing a CuBi2O4 thin film electrode, and the specific steps are as follows:
[0069] (1) 5 mmol of copper acetate and 5 mmol of sodium acetate were dissolved in 100 ml of deionized water to obtain electrolyte I. FTO was immersed in electrolyte I and a bias voltage of -0.2 V was applied to FTO. The electrodeposition time was 120 s to obtain a Cu2O thin film electrode.
[0070] (2) To 99 ml of 0.2 mol / L bismuth nitrate solution, add 1 ml of triethanolamine, a complexing agent, to obtain emulsion II.
[0071] (3) Add 0.05 mol KOH to the emulsion II in step (2) to obtain a clear solution III.
[0072] (4) The molar concentration of KNO3 in the clear solution III is controlled to be 1 mol / L. The molar concentration of KNO3 in the clear solution III is calculated to be 0.5 mol / L, which is less than 1 mol / L. Therefore, molten salt KNO3 is added to the clear solution III under strong stirring to obtain solution IV.
[0073] (5) The Cu2O thin film electrode obtained in step (1) is pulled and immersed in the solution IV obtained in step (4) at a speed of 0.2 cm / s, and then annealed at a temperature of 450°C for a reaction time of 2 h; the electrode is rinsed with deionized water and dried at 50°C for 3 h to obtain a CuBi2O4 thin film electrode.
[0074] The X-ray crystal diffraction pattern of the Cu2O prepared in Example 4 and the scanning electron microscope image of the Cu2O thin film electrode prepared are similar to those in Example 1.
[0075] The photoelectrocatalytic performance of the CuBi2O4 thin film electrode prepared in Example 4 is weaker than that in Example 1, indicating that the reduction of Cu 2+ Concentration, increase Bi 3+ ions, and the performance of the Bi-rich sample prepared is slightly inferior to that of pure CuBi2O4.
[0076] Comparative Example 1
[0077] This comparative example 1 provides a method for preparing a CuBi2O4 thin film electrode without KNO3 participating in the reaction and using commercial bismuth hydroxide, and the specific steps are as follows:
[0078] (1) Dissolve 10 mmol of copper acetate and 10 mmol of sodium acetate in 100 ml of deionized water to obtain electrolyte I; immerse FTO in electrolyte I of step (1), apply a bias voltage of -0.2 V to the FTO, and electrodeposit for 120 s to obtain a Cu2O thin film electrode.
[0079] (2) Add 10 mmol of bismuth hydroxide to 100 ml of deionized water to obtain emulsion II.
[0080] (3) Add 0.5 ml of triethanolamine as a complexing agent to the emulsion II in step (2) to obtain emulsion III.
[0081] (4) The Cu2O thin film electrode obtained in step (1) is pulled and immersed in solution III obtained in step (3) at a speed of 0.5 cm / s, and then annealed at a temperature of 450°C for a reaction time of 2 hours. The obtained electrode is rinsed with deionized water and dried at 50-80°C for 3 hours to obtain a CuBi2O4 thin film electrode.
[0082] The X-ray crystal diffraction pattern of the Cu2O prepared in this comparative example and the scanning electron microscope image of the Cu2O thin film electrode prepared are similar to those in Example 1.
[0083] The X-ray crystal diffraction pattern of the thin film electrode prepared in this comparative example is as follows Figure 7 As shown, the characteristic diffraction peaks of the PDF standard cards CuO-JCPDS No.80-1916 and Bi2O3-JCPDS No.71-0465 completely correspond, indicating that the sample is a mixed phase of CuO and Bi2O3, and the CuBi2O4 thin film electrode could not be prepared.
[0084] In this comparative example, ready-made bismuth hydroxide was directly used, which completely avoided the introduction of KNO3 molten salt. The specific influence of KNO3 molten salt on this reaction was explored. The conclusion is that without the participation of KNO3 molten salt, the degree of freedom of the reaction cannot be achieved, the various substances cannot be fully contacted, and the reaction cannot proceed normally.
[0085] The scanning electron microscope image of the thin film electrode prepared in this comparative example is as follows Figure 8 As shown, the surface of the CuO thin film electrode contains Bi2O3 nanosheets.
[0086] The photoelectrocatalytic performance of the thin film electrode prepared in this comparative example is as follows Fig. 9 As shown in the figure, when the concentration of KON is 0 mol / L (0 M), the prepared thin film electrode has a high conductivity at 39 mW / cm 2 , under 455nm monochromatic light, tested in an electrolyte environment of 0.5MHBO3 (pH=9) containing H2O2, it has a potential of 1.25mA / cm at 0.6V 2 The photocurrent density.
[0087] Comparative Example 2
[0088] This comparative example provides a method for preparing a CuBi2O4 thin film electrode, and the specific steps are as follows:
[0089] (1) 10 mmol of copper acetate and 10 mmol of sodium acetate were dissolved in 100 ml of deionized water to obtain electrolyte I; FTO was immersed in electrolyte I, a bias voltage of -0.2 V was applied to FTO, and the electrodeposition time was 120 s to obtain a Cu2O thin film electrode.
[0090] (2) To 95 ml of 0.05 mol / L bismuth nitrate solution, add 5 ml of triethanolamine, a complexing agent, to obtain emulsion II.
[0091] (3) Under vigorous stirring, add 0.05 mol potassium hydroxide to the emulsion II in step (2), and continue to stir vigorously for 30 minutes to obtain a clear solution III.
[0092] (4) Under strong stirring, 0.15 mol of molten salt KNO3 is added to the clarified solution III in step (3) to obtain solution IV.
[0093] (5) The Cu2O thin film electrode obtained in step (1) is pulled and immersed in the solution IV obtained in step (4) at a speed of 0.1 cm / s, and then annealed at a temperature of 450°C for a reaction time of 2 hours; the obtained electrode is rinsed with deionized water, and dried at 50-80°C for 3 hours to obtain a CuBi2O4 thin film electrode.
[0094] The X-ray crystal diffraction pattern of the Cu2O prepared in this comparative example and the scanning electron microscope image of the Cu2O thin film electrode prepared are similar to those in Example 1.
[0095] The scanning electron microscope image of the CuBi2O4 thin film electrode prepared in this comparative example is as follows: Fig.10 As shown. A CuBi2O4 thin film electrode can be prepared with a concentration of 2 mol / L KNO3, but it can be seen from the scanning electron microscope image that the CuBi2O4 in most areas has fallen off, because when a large amount of KNO3 molten salt is introduced into the reaction, the reaction freedom is too high, and the molten salt rolls on the electrode surface, causing the electrode to fall off.
Claims
1. A method for preparing a CuBi2O4 thin film electrode, characterized in that: The following steps are involved: (1) adding copper acetate and sodium acetate to deionized water and mixing evenly to obtain electrolyte I, placing FTO in electrolyte I, and obtaining a Cu2O thin film electrode by electrodeposition; (2) adding a complexing agent to the bismuth nitrate solution to obtain an emulsion II; (3) adding KOH to the emulsion II in step (2) to obtain a clear solution III containing bismuth hydroxide and potassium nitrate; (4) adjusting the molar concentration of potassium nitrate to 0.25-1 mol / L on the basis of the clarified solution III to obtain solution IV; (5) The Cu2O thin film electrode obtained in step (1) is pulled and immersed in solution IV obtained in step (4), and then annealed. The annealed electrode is washed with deionized water and dried to obtain a CuBi2O4 thin film electrode.
2. The method for preparing the CuBi2O4 thin film electrode according to claim 1, characterized in that: The molar concentration of copper acetate in the electrolyte I of step (1) is 0.05 mol / L to 0.2 mol / L, the molar concentration of sodium acetate is 0.05 mol / L to 0.2 mol / L, and the molar ratio of copper acetate to sodium acetate is 1:
1.
3. The method for preparing the CuBi2O4 thin film electrode according to claim 1, characterized in that: The conditions of the electrodeposition method in step (1) are: applying a bias voltage of -0.2 V to the FTO substrate and the electrodeposition time is 120 s.
4. The method for preparing the CuBi2O4 thin film electrode according to claim 1, characterized in that: In step (2), the volume ratio of the bismuth nitrate solution to the complexing agent is 95:5 to 99:1, the molar concentration of the bismuth nitrate solution is 0.05 mol / L to 0.2 mol / L; and the complexing agent is triethanolamine.
5. The method for preparing the CuBi2O4 thin film electrode according to claim 1, characterized in that: The amount of KOH added to the emulsion II in step (3) is 0.001-2 mol / L.
6. The method for preparing the CuBi2O4 thin film electrode according to claim 1, characterized in that: The pulling and dipping speed in step (5) is 0.05 to 0.5 cm / s.
7. The method for preparing the CuBi2O4 thin film electrode according to claim 1, characterized in that: In step (5), the annealing process temperature is 450° C. and the reaction time is 2 h; the drying temperature is 50-80° C. and the drying time is 3 h.
8. Use of the CuBi2O4 thin film electrode according to any one of claims 1 to 7 in photoelectrocatalytic water decomposition to produce hydrogen.
Citation Information
Cited By
Copper bismuthate / copper oxide conformal morphology heterojunction film and preparation method thereof
CN120158771A
Method for preparing bismuth cuprate nano-powder with assistance of fused salt
CN122233432A